2012
DOI: 10.1007/s12639-012-0218-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gastro intestinal parasites in ruminants and poultry in Telangana region of Andhra Pradesh

Abstract: The prevalence study was conducted on gastrointestinal parasites of cattle, buffalo, sheep, goat and poultry belongs to in and around Korutla, Karimangar district (Telangana region) of Andhra Pradesh. The prevalence of Fasciola sp., Amphistome sp., Eimeria sp. and Toxocara vitulorum in cattle and buffaloes were 5.3, 8.0, 10.0, 16.7 % respectively. The prevalence of Moniezia sp., Trichuris sp., Amphistome sp., Strongyle sp., Eimeria sp. in sheep and goat were 10.7, 8.0, 6.0, 9.3,4.7 % respectively. The prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 6 publications
(6 reference statements)
1
19
0
Order By: Relevance
“…The differences between time of sample collection and analysis as well as the specificity and sensitivity of the diagnostic methods employed by the various studies may also be possible reasons for the variations in the PPEs. Studies from Ethiopia [ 41 ] and Andhra Pradesh, India [ 42 ] also reported similar helminth species as those reported in Nigeria during the period under review.…”
Section: Discussionsupporting
confidence: 68%
“…The differences between time of sample collection and analysis as well as the specificity and sensitivity of the diagnostic methods employed by the various studies may also be possible reasons for the variations in the PPEs. Studies from Ethiopia [ 41 ] and Andhra Pradesh, India [ 42 ] also reported similar helminth species as those reported in Nigeria during the period under review.…”
Section: Discussionsupporting
confidence: 68%
“…Despite lack of statistical significant variation, the Bunaji and Kuri breeds of cattle were the most infected, similar to the previous observations made by Adedipe et al (2014 et al, 2006). In addition, the employment of bile sedimentation and faecal sedimentation and floatation had the added advantage of detecting more parasites than previously employed (Murthy and Rao, 2014), where only faeces were collected and faecal sedimentation and floatation techniques employed in the analyses. On sheep, the parasites recovered are typical of the study location and are similar to the previously reported parasites in sheep in Abuja (Jegede et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal parasites like helminths and protozoan are very common in sheep and goats. When heavy infections occur those parasites contribute to reduced milk and meat production (Murthy and Rao, 2014). Small ruminants under intensive and extensive production systems are extremely susceptible to the effects of wide range of helminths (Abede and Esayas, 2001).…”
Section: Introductionmentioning
confidence: 99%